Resonance Rayleigh Scattering Spectra of CdTe Quantum Dots-Dermatan Sulfate System and its Analytical Applications - Liu, Dan (Asian Journal of Chemistry, 2014)
In this paper, CdTe quantum dots with the diameter of 2-3 nm were synthesized in aqueous solution with cysteamine as stabilizing agent. The interaction between cysteamine-CdTe quantum dots and dermatan sulfate was studied by resonance Rayleigh scattering spectra. It showed that the intensities of resonance Rayleigh scattering of cysteamine-CdTe quantum dots-dermatan sulfate were enhanced greatly, the resonance Rayleigh scattering intensities (DIRRS) was directly proportional to the concentration of dermatan sulfate. The linear ranges and the detection limits were 0.0039-0.6 and 1.2 ng mL-1. The proposed methods exhibited higher sensitivity, so that they are more suitable for the determination of trace amounts dermatan sulfate. The optimum conditions, the influencing factors and the effects of coexisting substances on the reaction were investigated. The result indicated that the method can be applied to the determination of dermatan sulfate in serum and urine samples with satisfactory results. The reasons of resonance Rayleigh scattering enhancement were also discussed.